Response of Celery Plant Growth and Production (Apium Graveolens L.) to Liquid Organic Fertilizer Goat Urine - Maimunah Siregar; Suryani Sajar; Brendy Matalauta gm (Yayasan Sinergi Multidimensi Kreatif, 2024)
The increase in population has a great influence on the availability of land. As a result, there is a lot of degradation of productive land that should still be able to carry out agricultural activities. Along with the development of technology and the advancement of human civilization, humans began to look for solutions so that narrow yard land was still able to support family income. The purpose of this study is to determine the effect of liquid organic fertilizer of goat urine on the growth and production of Celery plants (Apium graveolens L.). The results of the study on the effect of the application of goat urine liquid organic fertilizer on the growth and production of celery plants had a real effect on the height of plants aged 1 and 2 MSPT, but had a very real effect on the age of 3 MSPT, The results of the variegated fingerprints showed a real effect on the application of goat urine liquid organic fertilizer on the number of seedlings, wet weight per sample and consumption weight per sample. Celery plants develop uniformly, thus allowing for better absorption of nutrients to encourage their growth. This shows that the application of Liquid Organic Fertilizer (POC) concentration is the most effective in encouraging plant growth and production